The effects of footwear midsole longitudinal bending stiffness on running economy and ground contact biomechanics: A systematic review and meta-analysis - Rodrigo-Carranza, V.; González-Mohíno, F.; Santos-Concejero, J.; González-Ravé, J. M. (European Journal of Sport Science, 2022)
This study aimed to address the effects of increased longitudinal being stiffness (LBS) on Running economy (RE) and running biomechanics. A systematic search on 4 electronic databases (Pubmed, WOS, Medline and Scopus) was conducted on May 26, 2021. Twelve studies (37 comparisons) met the inclusion criteria and were included in the meta-analysis. This resulted in 188 participants. Standardised mean difference with 95% confidence intervals (CI) between footwear with increased LBS vs. non-increased LBS conditions and effect sizes were calculated. To assess the potential effects of moderator variables (type of plate, increased LBS, length of the plate, shoe mass and running speed) on the main outcome variable (i.e., RE), subgroup analyses were performed. Increased LBS improved RE (SMD=-0.43 [95% CI -0.58, -0.28], Z=5.60, p<0.00001) compared to non-increased LBS. Significant increases of stride length (SMD = 0.29[95% CI 0.10, 0.49],Z=2.93, p=0.003) and contact time (SMD=0.17 [95% CI 0.03,0.31], Z=2.32,p=0.02) were found when LBS was increased. RE improved to a greater degree at higher running speeds when using shoes with increased LBS. RE improved 3.45% with curve plate compared to no-plate control condition without improvements with flat plate shoes. When shoe mass was matched between footwear with increased LBS vs. non-increased LBS conditions, RE improved (3.15%). However, when shoe mass was not controlled (experimental condition with~35 grams extra), a significant small improvement was found. Footwear with increased LBS improved RE. These RE improvements appear along with an increase of stride length and contact time. Shoe mass, type of plate (flat or curve) and running speed should be taken into consideration when designing a shoe aimed at improving long-distance running performance.